Images between reality and utopia: A curatorial narration - Wechsler, Diana B. (Re-visiones, 2024)
Three boxes of different sizes are placed in an ideal space. Each one defines its place. Though they were all made recently, the boxes seem like trunks of relics: silent, they hold keys to reviewing certain aspects of the history and cultural memory of Argentina.
Keywords: Essay; Art; Criticism